Preparation method and application of dual-mode nano-porous silver / silver-cobalt bimetallic series catalyst
Through the tandem catalytic action of the dual-mode nanoporous silver/silver cobalt bimetallic catalyst, the problem of difficulty in promoting the conversion of nitrate to nitrite and nitrite to ammonia at the same time is solved, and the efficiency of electrocatalytic nitrate reduction reaction is improved It has an ammonia synthesis capability, suitable for industrial applications.
Patent Information
- Application Number
- CN202411353536.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Existing single active site catalysts are difficult to accelerate the reduction reactions from nitrate to nitrite and nitrite to ammonia simultaneously, limiting the kinetic efficiency of electrocatalytic nitrate reduction reactions.
A two-phase catalyst with a two-phase structure was prepared by alloying-dealloyation method using a dual-mode nanoporous silver/silver cobalt bimetallic catalyst (np Ag/Ag-Co). The Ag phase accelerates the conversion of NO3- to NO2-, and Ag- The Co phase accelerates the conversion of NO2- to NH3, achieving tandem catalysis.
It improves the catalytic activity and efficiency of nitrate reduction reaction, simplifies the catalyst preparation process, is suitable for industrial production, and shows high-efficiency ammonia synthesis ability in electrocatalysis.
Smart Images

Figure CN119221026A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of synthesizing ammonia by electrocatalytic nitrate reduction reaction, and specifically relates to a preparation method and application of a dual-mode nanoporous silver / silver-cobalt bimetallic catalyst (np Ag / Ag-Co). Background Art
[0002] Nitrate (NO3 - ) is a common water pollutant. In recent years, with the excessive use of fertilizers and the excessive discharge of domestic and industrial sewage, the nitrate content in surface water and groundwater has gradually increased, posing a huge threat to the ecological environment and even human health. Therefore, it is urgent to develop an economical and efficient method for nitrate removal. In recent years, the electrocatalytic nitrate reduction reaction driven by renewable electricity has been considered an environmentally friendly nitrate removal method.
[0003] Ammonia (NH3), as a nitrate reduction product, is not only widely used in traditional agriculture, industry, military and medicine, but also has good development prospects in the field of new energy. The hydrogen content of NH3 is as high as 17.6wt%, and it is easy to liquefy, store and transport, so it is considered to be a potential carbon-free hydrogen energy carrier. At present, the large-scale production of NH3 in industry is mainly carried out by the Haber-Bosch process, which consumes about 1% of the world's energy supply and contributes about 1.3% of the world's carbon dioxide emissions. It is an energy-intensive industry. Moreover, the Haber-Bosch process requires high temperature and high pressure reaction conditions, and has high requirements for production equipment. For this reason, the development of environmentally friendly and sustainable NH3 synthesis processes has become a current research hotspot.
[0004] However, the nitrate reduction reaction (NO3 - RR) involves the transfer of eight electrons and nine protons. It is a complex reaction process and can be divided into NO3 - to nitrite (NO2 - ) and the initial reduction of NO2 - Subsequent reduction to NH3 in two steps. Rapid NO3 - RR needs to accelerate NO3 at the same time - To NO2 - , and NO2 - to NH3. However, catalysts with a single active site often cannot promote both reaction steps at the same time. Therefore, heterogeneous catalysts are designed to catalyze NO3 - To NO2 - and NO2 - To the reduction of NH3, realize the tandem catalytic process, thereby accelerating the overall NO3 -RR kinetics is a new strategy to improve catalyst activity. Summary of the invention
[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present disclosure provides a preparation method and application of a dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co.
[0006] According to a first aspect of the present disclosure, a method for preparing a dual-mode nanoporous silver / silver-cobalt bimetallic catalyst npAg / Ag-Co is provided, characterized in that the method comprises the following steps:
[0007] (1) using a dilute potassium hydroxide solution, a dilute hydrochloric acid solution, and a dilute nitric acid solution to clean 99.9% pure aluminum wire, 99.9% pure cobalt sheet, and 99.99% pure silver sheet, respectively, to remove the oxide layer on the metal surface;
[0008] (2) Weighing the cleaned aluminum, cobalt and silver at a preset atomic ratio of aluminum, cobalt and silver, respectively, placing the weighed aluminum, cobalt and silver in a vacuum melting furnace to form a metal alloy, and pumping to 3.0×10 -3 MPa vacuum, then use high-purity argon as a shielding gas, use an argon arc welding machine, repeatedly melt the metal alloy 5 times at an arc current of 220A until the alloy ingot has a uniform composition, and take out the alloy ingot after it cools to room temperature;
[0009] (3) The alloy ingot is placed in a high vacuum single-roller quenching and spinning machine and pumped to 9.0×10 -4 MPa vacuum, then using high-purity argon as a protective gas, melting the alloy ingot with a high-frequency current of 10A to obtain a molten alloy, and preparing the molten alloy into an alloy strip with a thickness of about 0.25 mm at a rotation speed of 2200 r / min;
[0010] (4) placing the alloy strip in a 1.0 M potassium hydroxide solution for dealloying treatment at room temperature for 5 hours, repeatedly washing the sample with deionized water until the pH value is 7.0, and then drying it in a vacuum drying oven at room temperature to finally obtain an np Ag / Ag-Co catalyst;
[0011] Preferably, in step (2), pure aluminum, pure cobalt and pure silver are weighed respectively according to the atomic ratio of Al:Co:Ag=84.0:14.4:1.6;
[0012] Preferably, the composition of the alloy strip in step (3) is Al 84.1 Co 14.3 Ag 1.6 ;
[0013] According to a second aspect of the present disclosure, there is provided an application of a dual-mode nanoporous silver / silver-cobalt bimetallic catalyst npAg / Ag-Co, characterized in that the catalyst is used for electrocatalytic nitrate reduction reaction to synthesize ammonia;
[0014] Preferably, the method comprises the following steps:
[0015] (1) An electrochemical performance test was conducted in an H-type electrolytic cell using an Ivium-n-Stat electrochemical workstation and a three-electrode system, wherein a carbon paper loaded with catalyst powder and a silver / silver chloride electrode were used as a working electrode and a reference electrode, respectively, and were placed in the cathode chamber of the H-type electrolytic cell; a high-purity platinum sheet was used as a counter electrode and was placed in the anode chamber of the H-type electrolytic cell; the cation chamber of the H-type electrolytic cell was separated by an N211 proton exchange membrane, and a 0.1 M potassium hydroxide solution containing 50 mM potassium nitrate was added to both chambers as an electrolyte, and high-purity argon gas was introduced before the test to remove impurity gases;
[0016] (2) electrochemical testing was performed using a chronoamperometry method, with a test potential range of +0.1 to -0.4 V vs. reversible hydrogen electrode (RHE) and a potential interval of 0.1 V vs. RHE. The test time at each potential was 2 hours, and then the electrolyte in the cathode chamber was collected;
[0017] (3) The electrolyte after the reaction was developed using the indophenol blue colorimetric method, and then the ammonium ion concentration in the electrolyte was calculated using a UV-visible spectrophotometer to calculate the NH3 yield YR and NH3 Faraday efficiency FE of the catalyst.
[0018] The purpose of the present invention is to prepare a np Ag / Ag-Co tandem catalyst with a two-phase structure and apply it to the electrocatalytic nitrate reduction reaction to synthesize NH3. The binary alloy phase diagram shows that silver (Ag) has an extremely low solubility in cobalt (Co), so that in the catalyst prepared by the alloying-dealloying method, Co metal and Ag metal form a two-phase separation structure of Ag and silver-cobalt bimetallic (Ag-Co). In addition, the three-dimensional porous structure makes the catalyst composed of a large number of ligaments, exposing abundant active sites, among which the Ag ligaments accelerate the conversion of NO3 to nitrite (NO2 - ), while the Ag-Co ligaments accelerated the conversion of NO2 - Subsequent conversion to NH3. This tandem catalysis accelerates the overall reaction kinetics and thus improves catalytic activity.
[0019] The innovation of this disclosure is:
[0020] (1) The preparation process of the np Ag / Ag-Co catalyst prepared in the present disclosure is simple, and industrial large-scale production can be achieved by simply increasing the volume of potassium hydroxide solution and the mass of the alloy strip;
[0021] (2) The np Ag / Ag-Co catalyst prepared in the present invention has an independent two-phase structure. The Ag phase realizes the conversion of nitrate to nitrite, and then the Ag-Co phase catalyzes the reduction of nitrite. The tandem catalytic effect of Ag and Ag-Co phases promotes the efficient synthesis of NH3.
[0022] (3) The np Ag / Ag-Co catalyst prepared in the present disclosure has a dual-mode nanoporous structure, in which the small-sized nanopores promote the NO3 - The adsorption and confinement of intermediates provide abundant active sites, while the large-sized pores accelerate the transport of reactants / products in and out of the electrode, which overall promotes the NO3 - RR. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. The accompanying drawings are used to better understand the present solution and do not constitute a limitation of the present disclosure. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, among which:
[0024] Figure 1 This is a scanning electron microscope (SEM) image of the np Ag / Ag-Co catalyst prepared in Example 1.
[0025] Figure 2 This is a high-resolution SEM image of the np Ag / Ag-Co catalyst prepared in Example 1.
[0026] Figure 3 This is a transmission electron microscope (TEM) image of the np Ag / Ag-Co catalyst prepared in Example 1.
[0027] Figure 4 This is the X-ray diffraction (XRD) pattern of the np Ag / Ag-Co catalyst prepared in Example 1.
[0028] Figure 5 Co 2p X-ray photoelectron spectroscopy (XPS) spectra of the np Ag / Ag-Co catalyst prepared in Example 1 and the np Co catalyst prepared in Comparative Example 1.
[0029] Figure 6 This is the Ag 3d XPS spectrum of the np Ag / Ag-Co catalyst prepared in Example 1.
[0030] Figure 7The np Ag / Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, the np Ag catalyst prepared in Comparative Example 2, and the Ag / Ag-Co nanoparticle catalyst prepared in Comparative Example 3 were subjected to NO3 degradation in the potential range of +0.1 to -0.4 V vs. RHE. - Image of RR’s NH3 YR test results.
[0031] Figure 8 The np Ag / Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, the np Ag catalyst prepared in Comparative Example 2, and the Ag / Ag-Co nanoparticle catalyst prepared in Comparative Example 3 were subjected to NO3 degradation in the potential range of +0.1 to -0.4 V vs. RHE. - Image of RR’s NH3 FE test results.
[0032] Fig. 9 The np Ag / Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, and the np Ag catalyst prepared in Comparative Example 2 were subjected to NO3 - RR NO2 - YR test result picture.
[0033] Fig.10 The np Ag / Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, and the np Ag catalyst prepared in Comparative Example 2 were subjected to NO3 - RR NO2 - FE test result picture.
[0034] Fig.11 The np Ag / Ag-Co catalyst prepared in Example 1 1 H NMR ( 1 1H NMR).
[0035] Fig.12 The np Ag / Ag-Co catalyst prepared in Example 1 was subjected to different NO3 concentrations. - NO3 in solution - RR test result picture.
[0036] Fig.13 This is a picture of the cyclic stability performance test results of the np Ag / Ag-Co catalyst prepared in Example 1.
[0037] Fig.14This is a SEM image of the np Ag / Ag-Co catalyst prepared in Example 1 after a 10-hour cycle stability test.
[0038] Fig.15 This is a high-resolution SEM image of the np Ag / Ag-Co catalyst prepared in Example 1 after a 10-hour cycle stability test. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0040] Example 1
[0041] Use dilute potassium hydroxide solution, hydrochloric acid solution and nitric acid solution to clean high-purity Al wire (purity: 99.9%), high-purity Co sheet (purity: 99.9%) and high-purity Ag sheet (purity: 99.99%) to remove the oxide layer on the metal surface. Weigh Al wire, Co sheet and Ag sheet according to the atomic ratio of Al: Co: Ag = 84.0: 14.4: 1.6, place the above metals in the crucible of the smelting furnace, and use high-purity argon (Ar) (purity: 99.999%) as the protective gas. Then set the voltage of the argon arc welding machine to 15V, and the corresponding arc current to 220A, so that the above metals are quickly melted at a temperature close to 3000°C to form a metal alloy. After heating for 30 seconds, remove the arc, and the temperature of the metal alloy ingot drops to about 200°C under the cooling effect of circulating water. Repeat the smelting 5 times to obtain an alloy ingot with uniform composition. Subsequently, in a high vacuum single-roller spinning quenching and spinning machine, the metal alloy ingot was placed at the center of a high-frequency coil with an induction current of 10A and re-melted in an Ar atmosphere. Under the action of circulating water, the molten metal was rapidly cooled on the surface of a copper roller with a rotation speed of 2200r / min to obtain an Al alloy with a thickness of 0.25mm. 84.1 Co 14.3 Ag 1.6 The alloy strip was finally immersed in 200 mL of 1.0 M potassium hydroxide solution and subjected to dealloying treatment for 5 hours at room temperature, and then the alloy strip was crushed into metal powder under the action of ultrasound. The obtained powder was repeatedly rinsed with deionized water to obtain the np Ag / Ag-Co catalyst.
[0042] Comparative Example 1
[0043] The cleaned Al wire and Co sheet were weighed respectively according to the atomic ratio of Al:Co=84.0:16. The other preparation methods were consistent with Example 1 to obtain an np Co catalyst.
[0044] Comparative Example 2
[0045] The cleaned Al wire and Ag sheet were weighed respectively according to the atomic ratio of Al:Ag=84.0:16. The other preparation methods were consistent with Example 1 to obtain an np Ag catalyst.
[0046] Comparative Example 3
[0047] 0.7858 g of cobalt nitrate hexahydrate and 0.0510 g of silver nitrate were dissolved in 20 mL of deionized water, and the metal ions were evenly dispersed under magnetic stirring, and then 20 mL of aqueous solution containing 0.2270 g of sodium borohydride was added to the solution. The mixed solution was then kept at room temperature at a stirring speed of 600 r / min for 5 minutes. Finally, the sample was obtained by centrifugation and washed several times with deionized water and anhydrous ethanol to remove impurities to obtain Ag / Ag-Co nanoparticles (Ag / Ag-Co NPs).
[0048] Figure 1 The SEM image of the np Ag / Ag-Co catalyst prepared in Example 1. As shown in the figure, the np Ag / Ag-Co catalyst presents a three-dimensional nanoporous structure with pores with a diameter of about 200 nm. Figure 2 This is a high-resolution SEM image of the np Ag / Ag-Co catalyst prepared in Example 2. As shown in the figure, the surface of the np Ag / Ag-Co catalyst has uniformly distributed small-sized pores with a diameter of about 10 nm.
[0049] Figure 3 This is a TEM image of the np Ag / Ag-Co catalyst prepared in Example 2. The tiny pores in the image further illustrate that the catalyst has a nanoporous structure. The high-resolution TEM image shows that the lattice spacing of the small-sized ligaments and the large-sized ligaments are 0.205nm and 0.238nm, respectively, corresponding to the Co(111) and Ag(111) crystal planes, respectively. In addition, according to the binary phase diagram, Ag has an extremely low solubility in Co. Therefore, during the dealloying process, most Ag atoms spontaneously separate to form Ag ligaments distributed around the Ag-Co matrix, with a diameter in the range of 30 to 50nm, so that the catalyst has a two-phase structure of Ag and Ag-Co.
[0050] Figure 4The figure is the XRD spectrum of the np Ag / Ag-Co catalyst. The diffraction peak of the catalyst at 2θ of 44.2° corresponds to the Co(111) crystal plane with PDF card number 15-0806, and the diffraction peaks at 2θ of 38.116°, 64.4°, 77.5° and 81.5° correspond to the Ag(111), (220), (311) and (222) crystal planes with PDF card number 04-0783, respectively, indicating that the np Ag / Ag-Co catalyst prepared in Example 1 has a coexistence structure of Co and Ag.
[0051] X-ray photoelectron spectroscopy analysis was performed for the np Ag / Ag-Co catalysts to determine the chemical states of the catalyst surface components. Figure 5 Co 2p pictures and Figure 6 The Ag 3d spectra of np Ag / Ag-Co catalysts show that Co and Ag exist in metallic state. 3 / 2 The binding energy of Ag (778.10 eV) shifts negatively (~0.3 eV), indicating that the presence of Ag causes electron transfer from Ag to Co.
[0052] The np Ag / Ag-Co catalyst prepared in Example 1 was subjected to atomic inductively coupled plasma spectroscopy testing, which can determine the content of metal elements in the catalyst. The atomic ratio of Co to Ag in the np Ag / Ag-Co catalyst is 90.7:9.3.
[0053] Example 2
[0054] The np Ag / Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, the np Ag catalyst prepared in Comparative Example 2, and the Ag / Ag-Co NPs catalyst prepared in Comparative Example 3 were electrocatalyzed to generate NO - RR test, using Ivium-n-Stat electrochemical workstation, adopts three-electrode system, and conducts electrochemical performance test in H-type electrolytic cell, wherein carbon paper loaded with catalyst powder and silver / silver chloride electrode are used as working electrode and reference electrode respectively, and are placed in the cathode chamber of H-type electrolytic cell; high-purity platinum sheet is placed in the anode chamber of H-type electrolytic cell as counter electrode. The positive and negative chambers of H-type electrolytic cell are separated by N211 proton exchange membrane, and 0.1M potassium hydroxide solution containing 50mM potassium nitrate is added to both chambers as electrolyte, and high-purity argon gas is introduced before the test to remove impurity gas; then the electrochemical test is conducted by chronoamperometry, and the test potential range is +0.1~-0.4Vvs. reversible hydrogen electrode (RHE), the potential interval is 0.1V vs.RHE, the test time is 2 hours at each potential, and then the electrolyte in the cathode chamber is collected.
[0055] Example 3
[0056] Weigh 0.8 g of sodium hydroxide, 1.156 g of salicylic acid and 1.3174 g of trisodium citrate dihydrate respectively, and fully dissolve them in 20 mL of deionized water to obtain color developer 1; absorb 70 μL of sodium hypochlorite solution (effective chlorine content: 7.5%, free alkali content: 0.1-1%), and fully dissolve it in 20 mL of deionized water to obtain color developer 2; weigh 0.0341 g of sodium nitroprusside, and fully dissolve it in 3 mL of deionized water to obtain color developer 3.
[0057] Example 4
[0058] Take the NO3 in Example 2 - The cathode electrolyte of RR was diluted with 0.1M potassium hydroxide solution by an appropriate multiple, and 2mL of electrolyte was taken. 2mL of color developer 1, 1mL of color developer 2 and 0.2mL of color developer 3 were added in sequence. After shaking evenly, it was allowed to stand at room temperature in the dark for 2 hours. The absorbance at a wavelength of 655.4nm was then tested by a UV-visible spectrophotometer, and the ammonium ion concentration in the electrolyte was calculated based on the fitted standard curve, and the NH3 YR and NH3FE of the catalyst were further calculated.
[0059] Figure 7 as well as Figure 8 The electrocatalytic NO3 of the np Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, the np Ag catalyst prepared in Example 2, and the Ag / Ag-Co NPs catalyst prepared in Comparative Example 3 - RR performance comparison. It can be seen from the figure that the NH3 YR and NH3 FE of the np Ag / Ag-Co catalyst are higher than those of the np Co and np Ag catalysts at each potential. When the test potential is -0.3 V vs. RHE, the NH3 YR and NH3 FE are 25.1 mg h -1 mg cat. -1 and 97.1%. In addition, the NO3 - The RR performance is significantly better than that of Ag / Ag-Co NPs, which further indicates that the porous structure is beneficial to NO3 - RR is carried out.
[0060] Example 5
[0061] Weigh 0.04 g of naphthylethylenediamine hydrochloride and 0.8 g of sulfonamide respectively, fully dissolve them in 10 mL of deionized water, and add 2 ml of concentrated phosphoric acid (85.0%) solution to obtain color developer 4.
[0062] Example 6
[0063] Take the NO3 in Example 2 - The cathode electrolyte of RR was acidified with concentrated phosphoric acid solution (85.0%) and diluted with 0.1M potassium hydroxide solution by appropriate multiples. Then 5mL of electrolyte was added with 0.1mL of color developer 4, and after shaking evenly, it was allowed to stand at room temperature in the dark for 20 minutes. Then, the absorbance at a wavelength of 540.0nm was tested by UV-visible spectrophotometer, and the NO2 in the electrolyte was calculated according to the fitted standard curve. - ion concentration, and further calculate the NO2 - YR and NO2 - FE.
[0064] Fig. 9 as well as Fig.10 The np Ag-Co catalyst prepared in Example 1, the np Co catalyst prepared in Comparative Example 1, and the np Ag catalyst prepared in Example 2 produced NO2 - Performance comparison. As can be seen from the figure, np Ag promotes NO3 - NO3 in RR process - To NO2 - conversion.
[0065] Example 7
[0066] The isotope labeling method was used in the experiment to explore the source of the product NH3. Fig.11 As shown, when using 15 When KNO3 is used as a reactant, 1 H NMR can detect 15 NH4 + Two corresponding groups of signal peaks; when using 14 When KNO3 is used as a reactant, 1 H NMR can detect 14 NH4 + Corresponding three groups of signal peaks; in order to exclude the influence of other factors in the electrolyte, we use a NO3-free - 0.1M potassium hydroxide solution was used as the reactant, and the results showed that no NH4 + The above results prove that the NH3 in the reaction product comes from NO3 in the electrolyte. - , rather than from external pollution.
[0067] Example 8
[0068] A 0.1 M potassium hydroxide solution containing 2 mM, 5 mM, 10 mM, 20 mM, 100 mM, 200 mM and 500 mM potassium nitrate was prepared as the electrolyte. The other operation steps were consistent with Example 2. The np Ag / Ag-Co catalyst was tested at different concentrations of NO3 - NO3 - RR catalytic activity.
[0069] Fig.12 The np Ag / Ag-Co catalyst prepared in Example 1 was subjected to different NO3 concentrations. - NO3 - RR catalytic activity test results, as shown in the figure, np Ag / Ag-Co catalyst in a wide range of NO3 - The excellent catalytic activity was maintained in the electrolyte, indicating that the np Ag / Ag-Co catalyst prepared in Example 1 has broad application prospects in the fields of NH3 synthesis and wastewater treatment.
[0070] Example 9
[0071] The cyclic stability of the np Ag / Ag-Co catalyst prepared in Example 1 was tested at a test potential of -0.3 V vs. RHE using a 0.1 M potassium hydroxide solution containing 50 mM potassium nitrate as the electrolyte. Fig.13 As shown, the catalyst maintained stable NH3 YR and NH3 FE after 10 hours of cycle test. Fig.14 as well as Fig.15 The SEM images show that the catalyst maintains its nanoporous structure after the cycle test, indicating that the catalyst has excellent stability.
[0072] Although the embodiments of the present disclosure have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. For those skilled in the art, the present disclosure may have various modifications and variations. Any changes, modifications, substitutions, combinations, and simplifications made to the present disclosure shall be equivalent replacement methods and shall be included in the protection scope of the present disclosure.
Claims
1. A method for preparing a dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co, characterized in that: The following steps are involved: (1) using a dilute potassium hydroxide solution, a dilute hydrochloric acid solution, and a dilute nitric acid solution to clean 99.9% pure aluminum wire, 99.9% pure cobalt sheet, and 99.99% pure silver sheet, respectively, to remove the oxide layer on the metal surface; (2) Weighing the cleaned aluminum wire, cobalt sheet and silver sheet respectively according to the preset atomic ratio of aluminum, cobalt and silver, placing the weighed aluminum wire, cobalt sheet and silver sheet in a vacuum melting furnace to form a metal alloy, and pumping to 3.0×10 -3 MPa vacuum, then use high-purity argon as a shielding gas, use an argon arc welding machine, repeatedly melt the metal alloy 5 times at a current of 220A until the alloy ingot has a uniform composition, and take out the alloy ingot after it cools to room temperature; (3) The alloy ingot is placed in a high vacuum single-roller quenching and spinning machine and pumped to 9.0×10 -4 MPa vacuum, then using high-purity argon as a protective gas, melting the alloy ingot with a high-frequency current of 10A to obtain a molten alloy, and preparing the molten alloy into an alloy strip with a thickness of about 0.25 mm at a rotation speed of 2200 r / min; (4) The alloy strip was placed in a 1.0 M potassium hydroxide solution for dealloying treatment at room temperature for 5 hours, and the sample was repeatedly washed with deionized water until the pH value was 7.0, and then dried in a vacuum drying oven at room temperature to finally obtain an np Ag / Ag-Co catalyst.
2. The method for preparing the dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co according to claim 1, characterized in that: In step (2), pure aluminum, pure cobalt and pure silver are weighed respectively according to the atomic ratio of Al:Co:Ag=84.0:14.4:1.
6.
3. The method for preparing the dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co according to claim 1, characterized in that: The composition of the alloy strip in step (3) is Al 84.1 Co 14.3 Ag 1.6 .
4. The use of the dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co according to claim 1, characterized in that: The catalyst is used for synthesizing ammonia through electrocatalytic nitrate reduction reaction.
5. The use of the dual-mode nanoporous silver / silver-cobalt bimetallic catalyst np Ag / Ag-Co according to claim 4, comprising the following steps: (1) An electrochemical performance test was conducted in an H-type electrolytic cell using an Ivium-n-Stat electrochemical workstation and a three-electrode system, wherein a carbon paper loaded with catalyst powder and a silver / silver chloride electrode were used as a working electrode and a reference electrode, respectively, and were placed in the cathode chamber of the H-type electrolytic cell; a high-purity platinum sheet was used as a counter electrode and was placed in the anode chamber of the H-type electrolytic cell; the cation chamber of the H-type electrolytic cell was separated by an N211 proton exchange membrane, and a 0.1 M potassium hydroxide solution containing 50 mM potassium nitrate was added to both chambers as an electrolyte, and high-purity argon gas was introduced before the test to remove impurity gases; (2) electrochemical testing was performed using a chronoamperometry method, with a test potential range of +0.1 to -0.4 V vs. reversible hydrogen electrode (RHE) and a potential interval of 0.1 V vs. RHE. The test time at each potential was 2 hours, and then the electrolyte in the cathode chamber was collected; (3) The electrolyte after the reaction was developed using the indophenol blue colorimetric method, and then the ammonium ion concentration in the electrolyte was calculated using a UV-visible spectrophotometer to calculate the NH3 yield YR and NH3 Faraday efficiency FE of the catalyst.
Citation Information
Cited By
A CuOs / CdS / SSS photocathode, its preparation method and application
CN119932631B
Ag-FeOOH electrocatalyst, hydrogel enhanced electrocatalytic electrode as well as preparation method and application of Ag-FeOOH electrocatalyst and hydrogel enhanced electrocatalytic electrode
CN121781210A
